2019
DOI: 10.2478/anre-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Composite Index of Anthropometric Failure (CIAF) among Sonowal Kachari tribal preschool children of flood effected region of Assam, India

Abstract: Undernutrition is considered to be a serious public health problem in most of the developing countries. Globally, the anthropometric measures are widely used to estimate the magnitude of undernutrition in children. The Composite Index of Anthropometric Failure (CIAF) provides the overall magnitude of undernutrition as an aggregate single measure over the conventional anthropometric indices and helps in identification of single or double or multiple anthropometric failures in preschool children. The present inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(79 reference statements)
3
4
2
Order By: Relevance
“…Similarly, studies conducted in Ethiopia 31 and Nepal 29 reported higher prevalence, whereas studies from Zimbabwe and Peru reported lower prevalence of CIAF 32 . The ndings of this study align with the ndings of previous studies 26,27,28,29 and show that stunting is the most prevalent type of undernutrition. These ndings suggest that 16.6% of children experienced both stunting and underweight, indicating the coexistence of both acute and chronic undernutrition and emphasizing the importance of a composite index to gauge the scale of undernutrition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, studies conducted in Ethiopia 31 and Nepal 29 reported higher prevalence, whereas studies from Zimbabwe and Peru reported lower prevalence of CIAF 32 . The ndings of this study align with the ndings of previous studies 26,27,28,29 and show that stunting is the most prevalent type of undernutrition. These ndings suggest that 16.6% of children experienced both stunting and underweight, indicating the coexistence of both acute and chronic undernutrition and emphasizing the importance of a composite index to gauge the scale of undernutrition.…”
Section: Discussionsupporting
confidence: 91%
“…This study attempted to estimate the overall burden of child undernutrition at the national level by calculating CIAF and the factors contributing to the rich-poor gap in the prevalence of CIAF. The overall prevalence of CIAF was reported as 48.1%, which was in line with the estimates reported by studies conducted in Assam and Bangladesh 26,27 . However, studies conducted in states of Odisha, West Bengal and Chhattisgarh reported higher prevalence of CIAF [28][29][30] .…”
Section: Discussionsupporting
confidence: 88%
“…26 This underscores that children in the critical age-group contribute to high burden of undernutrition among children younger than 5 years. Work done by Bharali et al 27 identified 51% CIAF among tribal children aged 2 to 5 years, lesser compared to our estimate, while Mandal and Bose 28 reported more than 70% manifestation of CIAF. In comparison to Z scores, CIAF draws attention to the greater proportion of the population who suffer from multiple manifestations of undernutrition.…”
Section: Discussioncontrasting
confidence: 88%
“…Various scholars have used the CIAF among specific communities to understand undernutrition’s total prevalence. Bharali, Singh and Mondal (2019) constructed a CIAF to assess the spread of undernourishment among preschool children of the Sonowal Kachari tribe in a flood-affected region of Assam and reported a higher magnitude of undernutrition based on CIAF over conventional anthropometric measures. They observed the overall prevalence of wasting, underweight, stunting and CIAF to be 11.6%, 22.9%, 36.2% and 48.6%, respectively.…”
Section: Review Of Literaturementioning
confidence: 99%
“…For Darjeeling District of West Bengal, Sen and Mondal (2012) calculated the percentage of children in group E + F as 34.1 and group B + C + D + Y as 29.5. Bharali et al (2019) calculated the percentage of children in group E + F as 34.2 and group B + C + D + Y as 14.4 in a study conducted among Sonowal Kachari preschool children of flood-affected areas of Assam. The pattern is similar for the northeastern states as a whole, as observed by Ao and Lhungdim (2014), where they calculated the percentage of children in group E + F as 38.8 and group B + C + D + Y as 17.2.…”
mentioning
confidence: 99%